2014
DOI: 10.1021/jp500507a
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hydrogen on the Adsorption Behavior of Carboxylic Acid on TiO2 Surfaces

Abstract: In this work, we present binding energies of acetic acid on the (110), (100), and (011) surfaces of rutile TiO 2 calculated with the two density functional theory (DFT) exchange-correlation functionals PBE and PBEsol. It is shown that the binding energies can be influenced, in this case slightly reduced for all three surfaces, via preadsorption of hydrogen. Additionally, we tested the performance of the densityfunctional based tight-binding (DFTB) method applied to these adsorbate systems. Analysis of the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 87 publications
(109 reference statements)
3
32
1
1
Order By: Relevance
“…It has been found that acetic acid can dissociatively adsorb at the surface, while the molecular adsorption is far less stable, and according to previous studies [21,38,39], as well as our own calculations, two most common configurations of acetate, i.e., monodentate and bridging bidentate, may occur, which are shown in Fig. 1(b) and (c), respectively.…”
Section: Resultssupporting
confidence: 67%
“…It has been found that acetic acid can dissociatively adsorb at the surface, while the molecular adsorption is far less stable, and according to previous studies [21,38,39], as well as our own calculations, two most common configurations of acetate, i.e., monodentate and bridging bidentate, may occur, which are shown in Fig. 1(b) and (c), respectively.…”
Section: Resultssupporting
confidence: 67%
“…Indeed, as illustrated in Table I, the values of ϕ, θ and φ agree very well with those obtained experimentally. Concerning the acidic hydrogen, it was found that location (1) was energetically somewhat more favorable, i.e. there is a preference for the bridging hydroxyl to be adjacent to the adsorbed benzoate.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] ). To date, most progress has been achieved for the simplest -COOH containing molecule, namely formic acid (HCOOH), on the prototypical rutile TiO 2 (110)(1×1) surface 2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the adsorption energies of N 3 dye, calculated using the Vienna ab initio simulation package with the framework of DFT (LDA and PBE0), is between 250 and 550 kJ/mol depending on the different configuration of N 3 dye adsorption on the anatase TiO 2 surface (Yang et al, 2015). On a bidentate configuration, which is the dominate configuration (Upadhyaya et al, 2013;Heckel et al, 2014;Pastore and De Angelis, 2010;De Angelis et al, 2011), the adsorption of acetic acid on TiO 2 is 186 and 240 kJ/mol respectively for anatase and rutile TiO 2 (Manzhos et al, 2015). These results confirm the values found in our study.…”
Section: Statistical Physics Methodsmentioning
confidence: 99%